Resisting power from the ‘white knots’ of language: myth and memory in Ricardo Piglia’s La ciudad ausente - Vargas Canchanya, Martín (2024)
This article analyses the aesthetic-ideological proposal of Ricardo Piglia’s novel La ciudad ausente (1992). The aim is to elucidate how this work rethinks the link between the subject and collective memory in the context of a dystopian post-conflict scenario defined by repression and censorship in the social sphere. In this respect, it is hypothesised that in Piglia’s work there is an effort to recompose social ties and to nourish a form of resistance to power through the re-actualisation of the mythical foundation of language (the ‘white knots’). In fiction, this enterprise is carried out by Macedonio’s machine, which gathers the signs of the past and constructs multiple horizons of meaning. In this process, this apparatus constitutes itself as a subject through discourse and adopts an enunciative praxis that questions, using fiction, the reality established by hegemonic narratives, appealing to myth and the unrepresentable character of language. Around it, a space opens up for the construction of utopia and the creation of a collective memory beyond the regime of meaning established by state power.